Achilles Tendon Repair: Can Patients Read, Understand, and Act on Online Educational Resources?. Issue 4 (22nd October 2020) - Gao, Burke; Shamrock, Alan G.; Gulbrandsen, Trevor; Femino, John E.; Netto, Cesar de Cesar; Duchman, Kyle R.
Category: Sports; Trauma Introduction/Purpose: Patients often access online resources to learn about orthopedic procedures prior to undergoing elective surgery. In order to be fully understood by the average English-speaking adult, online health information must be written at an elementary school reading level. To be helpful to patients, educational resources should also be generally understandable and have actionable direction that positively affects healthcare interactions. There are several previously validated indices for accessing the reading level of written materials. The Patient Education Materials Assessment Tool (PEMAT) provides a reliable and validated method to measure the understandability and actionability of education materials. The purpose of this study was to utilize PEMAT and readability algorithms to quantify readability, understandability and actionability of online patient education materials related to Achilles tendon repair. Methods: Online patient education materials were identified using two independently conducted Google engine searches with the term 'Achilles tendon repair'. Using the top 50 search results, articles were included if they specifically served to educate patients regarding TAA. Exclusion criteria included news articles, non-text materials (video), research manuscripts, industry websites, and articles not related to Achilles tendon repair. The readability of included articles was quantified using the validated Flesch-Kincaid Grade Level index. The PEMAT form for printed materials was used to assess understandability and actionability using a 0-100 scale for both measures of interest. Spearman's correlation coefficient was utilized to examine the relationship between a website's average rank on Google (from first to last) and its readability, understandability, and actionability. P-values of less than 0.05 were considered significant. Results: Thirty-one websites met inclusion criteria. The mean Flesch Kincaid reading grade level was 10.8+-2.9, with only one website written below the 6th grade reading level. Higher Flesch-Kincaid grade was associated with later Google seach rank (rho: 0.488, p=0.010). Mean understandability and actionability scores were 67.1+-16.4% and 38.3+-28.4%, respectively. Among understandability criteria, only 12.9% (n=4) of articles included summaries and just 38.7% (n=12) included visual aids. Among actionability categories, 74% (n=23) of websites identified at least one action for readers, while only 60.8% (n=14) of these studies broke down actions into explicit, easy to understand steps. Actionability scores were not correlated with Google search rank (rho: -0.02, p=0.888), while higher understandability scores were associated with later Google search rank (rho: 0.45, p=0.017). Conclusion: Only one website describing Achilles tendon repair was written at or below the nationally recommended 6th grade reading level. Overall, Achilles tendon repair online educational materials scored poorly with respect to readability, understandability, and actionability. Articles that appeared earlier in the Google search had lower readability and understandability scores. In the era of shared decision making, it is vital that patients understand procedures, as well as the risks and benefits prior to undergoing elective surgery. These results suggest that current publicly available resources for Achilles tendon repair remain inadequate for patient education.